Language and Movement Synchronization in Dyadic Psychotherapeutic Interaction – A Qualitative Review and a Proposal for a Classification - Scheidt, Carl Eduard; Pfänder, Stefan; Ballati, Arianna; Schmidt, Stefan; Lahmann, Claas (Frontiers in Psychology, 2021)
In individual psychotherapy verbal communication and movement synchronization are closely interrelated. The microanalysis of timing, rhythm and gestalt of movement has established dynamic movement coordination as a systemic property of the dyadic interaction. Movement synchronization supports and enhances the unfolding of linguistic meaning. In order to substantiate the importance of the concept of synchrony for adult psychotherapy we review evidence from developmental psychology and discuss approaches to measure synchrony with particular reference to the naturalistic setting of dyadic psychotherapy. As the concept of synchrony is still ambiguous, and the respective interactional phenomena are ephemeral and fluid in the current paper we suggest a set of five general dimensions for the description of synchronization and nine additional categories which specifically enable the classification of phenomena of movement synchronization. The five general dimensions are: (1) context, (2) resources, (3) modality, (4) entrainment and (5) time-lag. The eight categories for the description of movement synchrony are: (1) spatial direction, (2) amplitude, (3) sinuosity, (4) duration, (5) event structure, (6) phase, (7) frequency and (8) content. To understand the process of participatory sense-making and the emergence of meaning in psychotherapy, synchrony research has to cope with the multimodality of the embodied interaction. This requires an integrated perspective of movement and language. A system for the classification of synchrony phenomena may contribute to the linking of variations and patterns of movement with language and linguistic utterances.